Evaluasi Ketahanan Plasma Nutfah Talas Papua Terhadap Penyakit Hawar Daun Talas (Phytophthora colocasiae Rac.) - Frenki A. Paiki (Fakultas Pertanian Universitas Papua, 2009)
The aim of this experiment was to evaluate the resistant level of Papuan local taro germ plasma to the leaf blight disease as well as identify the resistant genotype. From 56 taro cultivars have been tested, only ten cultivars found resistant to leaf blight disease at week 16 while at week 26 it reduced to five cultivars only. These five resistance cultivars are UC-010, UC-015, UC-022, UC-043, and UC-085.